Glucose Tolerance Tests for Systematic Screening of Glucose Homeostasis in Mice. Issue 1 (2nd March 2015) - Rozman, Jan; Rathkolb, Birgit; Neschen, Susanne; Fuchs, Helmut; Gailus‐Durner, Valérie; Klingenspor, Martin; Wolf, Eckhard; Hrabě de Angelis, Martin
Abstract : This article presents a detailed description of intraperitoneal and oral glucose tolerance tests in mice. The former is widely used in initial high‐throughput phenotyping of mutant mice to assess a diabetic phenotype and alterations in glucose homeostasis. Each protocol provides a comprehensive description of each step in the workflow, including variation of the standard protocol under particular circumstances (e.g., sensitivity to food deprivation, excessive deviations in body composition, or need for extra blood samples for additional analyses). We also describe how reduction of body mass and body temperature can be used as additional readouts to monitor metabolic function in response to food deprivation. © 2015 by John Wiley & Sons, Inc.